A Corpus Based Transitivity Analysis of Newspaper Articles on Floods - Ahmad , Sumera Shan; Mahmood, Muhammad Asim; Azhar, Wardah (International Journal of Psychosocial Rehabilitation, 2020)
aim of the current research is to explore distributions and functions of six processes of transitivity analysis in flood related Newspaper articles. No matter a country is developed, developing or under developed, floods bring drastic results in the whole world without discrimination. They are one of major causes of social unrest. Since, newspapers can be considered as a good and authentic source of information, so a small corpus of twenty (20) English newspaper articles addressing the issue of floods in Pakistan has been collected for the above purpose. Data was analyzed by transitivity analysis proposed by Halliday and Matthiessen (2014). It has six functions which have been further subdivided into many functions to explore any text. This analysis helps out in finding writing patterns which are followed in writing newspaper articles on the topic of floods. This study explores which procedure they use to follow in order to convey such pieces of news and do they suggest possible strategies too to overcome them. The study reflects that material and mental processes remained more dominant in the data and with the help of them, usually media partners try to sensationalize the writings and blame government officials as responsible of this undesirable situation. Verbal, behavioral and existential processes have been used very little.